(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Previous morphological studies have found degenerative retinal abnormalities in experimental hypopinealism. It is important to determine the morphology and function of the iris and ciliary body in prolonged pineal gland dysfunction with melatonin deficiency. Purpose: To determine the morphology and function of the iris and ciliary body in rabbits maintained under conditions of prolonged around-the-clock illumination leading to hypopinealism and melatonin deficiency. Material and Methods: Fifty five adult rabbits (110 eyes) were used in this experimental study. Animals were divided into two groups, an experimental group of 32 animals maintained under conditions of around-the-clock illumination to induce functional hypopinealism, and a control group of 23 animals maintained under natural day/night cycle conditions. Both groups were subdivided into 5 subgroups based on the duration of the experiment: 1-2 months, 3-5 months, 8-12 months, 18-19 months, and) 26-28 months. Blood melatonin levels were assessed by an enzyme-linked immunosorbent assay. A comprehensive morphological study of rabbit iris and ciliary body specimens was conducted. Results. Blood melatonin level at night time in the experimental group was almost six-fold lower than blood melatonin level in the control group. In animals maintained under conditions of around-the-clock illumination, marked circulatory abnormalities with markedly dilated and hyperemic vessels were observed in the iris and ciliary body at time points until 12 months. In addition, at 12 to 28 months, iris and ciliary body vascular circulatory abnormalities appeared to be changed by sclerotic abnormalities. In animals exposed to around-the-clock illumination, vascular sclerotic changes appeared substantially earlier, and were much more marked, than in control animals. The mean vascular wall thickness (VWT) in iris and ciliary body specimens for the experimental group was 1.5-fold higher than that for the control group (177.5 ± 7.3×10-6 m vs 101.9 ± 4.4×10-6; р < 0.05) at 18 to 19 months, and twice higher than that for the control group (217.4 ± 8.7×10-6 m vs 107.2 ± 5.2 ×10-6 m) at 26 to 28 months. The like newly formed rough bundles of collagen fibers found in an analogue of the Schlemm canal may exert a very negative effect on hydrodynamics of the eye.